Street-gang and tribal-warrior autobiographies - Brumble, H. David (Anthem Press, 2018)
To drink of death : Tukup's head-hunter autobiography and the characteristics of tribal-warrior autobiography -- The kinds of street-gang autobiography -- The bubble reputation : honor, glory and status among the warriors -- Glory manifest : coup tales, warrior boasts and gangsta rap -- Brutal honesty -- The education of the warrior -- The warrior choice -- Mona Ruiz's two badges : women warriors and warriors' women -- Sam Blowsnake and the unfortunate Pottawatomie -- The gangbanger autobiography of Monster Kody (AKA Sanyika Shakur) -- Battle, raid and stratagem -- Berserkers and the tragedy of warrior individualism.